Réponses

2013-12-17T18:49:53+01:00
Bonsoir

a) 15x² - 26x = 0
x(15x - 26) = 0
x = 0  ou  15x - 26 = 0 
x = 0  ou  15x = 26 
x = 0  ou  x = 26/15
S = {0 ; 26/15}

b) 16y² - 49 = 0
(4y)² - 7² = 0
(4y - 7)(4y + 7) = 0
4y - 7 = 0   ou     4y + 7 = 0
4y  = 7      ou     4y = -7
y = 7/4      ou     y = -/4
S = {7/4 ; -7/4}

c) 100a² + 60a + 9 = 0
(10a + 3)² = 0
10a + 3 = 0
10a = -3
a = -3/10
S = {-3/10}

d) (3y + 4)² - (2y - 3)² = 0
[(3y + 4) + (2y - 3)] 
[(3y + 4) - (2y - 3)]  + 0
(3y + 4 + 2y - 3)(3y + 4 - 2y + 3) = 0
(5y  + 1)(y + 7) = 0
5y + 1 = 0   ou   y + 7 = 0
5y = -1        ou   y = -7
y = -1/5      ou   y = -7
S = {-1/5 ; -7}